2010
DOI: 10.1002/oa.1219
|View full text |Cite
|
Sign up to set email alerts
|

Looking for problems: A systems approach to hominin palaeocommunities from Plio‐Pleistocene Africa

Abstract: This paper evaluates the potential contribution(s) of faunal analysis to hominin palaeoecology at regional and continental scales, through an explicit investigation of the values, methods and conceptual frameworks of palaeoanthropology and their compatibility with real data structures. It employs a problem-framing method developed in policy-relevant science to establish a suitable research design for 'large scale' faunal analysis, before testing the method in a pilot study of 48 faunal assemblages from the Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…The transition from closed to semi-open habitats proposed by most theories (see Figure 1) for example, cannot be identified in the fossil record without ambiguity. The earliest hominin sites are located in woodlands (Pickford & Senut 2001;White et al 2009) and mixed habitats (Vignaud et al 2002) with later ones across the full habitat spectrum (Winder 2012).…”
Section: Limitations Of Existing Hypothesesmentioning
confidence: 99%
“…The transition from closed to semi-open habitats proposed by most theories (see Figure 1) for example, cannot be identified in the fossil record without ambiguity. The earliest hominin sites are located in woodlands (Pickford & Senut 2001;White et al 2009) and mixed habitats (Vignaud et al 2002) with later ones across the full habitat spectrum (Winder 2012).…”
Section: Limitations Of Existing Hypothesesmentioning
confidence: 99%
“…Gene flow across taxon boundaries (particularly, although not exclusively, between closely related species or sub-species) is common among the primates (Arnold, 2009), and fuels debate about primate taxonomy. There are two primate groups that are regularly used as comparators for studies of human evolution: (1) the papionins, which have been identified as a rich source of potential analogies for early hominin evolution (Elton, 2006;Jolly, 1970Jolly, , 2001Winder, 2012) and (2) the non-human apes, our closest living relatives. This section explores the comparative evidence first and then moves on to the direct data.…”
Section: Introductionmentioning
confidence: 99%
“…Rodents, the quintessential lab mammals, are also ready candidates for studies in the natural world. A principal obstacle to using faunal assemblages for reconstruction of paleoenvironments is taphonomic bias (Winder, 2012). However, rodents are typically rselected organisms, and reproduce early and often (Churakov et al, 2010).…”
Section: Rodent Incisors As a Proxymentioning
confidence: 99%